THE EMERGENCE OF ENVIRONMENTAL PROBLEMS IN THE STATE OF ACRE AND THE RELATIONSHIP OF THE ACRE PEASANTRY WITH NATURE - da Silva, Mauro Cesar Rocha (Seven Editora, 2025)
In the 1970s, social conflicts broke out in the countryside due to the emergence of new interests that shifted the positioning of agents in the social fabric towards development. The Rubber Tappers Movement emerged from these conflicts, bringing environmental issues to the forefront, which gave visibility to concerns about preserving rubber and chestnut forests. Nature began to appear as a strategic resource to be considered in the formulation of development policies. Resolving the conflicting interests of agents was the great challenge to be overcome. This article seeks to demonstrate how the scope of a political project germinated in the quicksand of Acrean society, which, based on natural resources, managed to respond to conflicts and to use nature as a supporting principle to establish Acre’s development. The aim is to find out what sentiment the future Forest Government drew on to complete its political project. DOI: https://doi.org/10.56238/sevened2025.026-004